AGING CHARACTERISTIC AND MECHANICAL PROPERTIES OF FORMED MG-ZN-AL-RE-CA ALLOYS - Antara, I Nyoman Gde (Jurnal Energi Dan Manufaktur, 2012)
Abstrak The present study focused on aging characteristic and mechanical properties of semi solid formed Mg-Zn-Al-RE-Ca alloys. The alloys are divided into Mg-8%Zn-4%Al-0.6%Ca and Mg-6%Zn-3%Al-0.6%Ca based alloys, and rare earth elements were added in the range from 1 to 3 mass% (hereafter ZAE841, ZAE842, ZAE843 and ZAE631, ZAE632, ZAE633). The alloy specimens were strained, press-formed at 580?C and extracted to prepare specimens for T-6 heat treatment and tensile investigations. The results show that all of the alloys exhibit microstructure that consisting of fine spherical ? particles and fine eutectic compounds around the particles. The peak hardness of the alloys was mainly reached when the solution heat treatment is conducted at temperature of 330?C for 16 hours and aging at 175?C for 32 hours. The hardness numbers increase with increasing content of the alloying elements. Tensile properties at high temperature of semi-solid formed alloys increase in accordance with increasing the amount of compounds. The amounts of compound increase as the alloying element increase.
Keywords: Mg-Zn-Al-RE-Ca alloys, aging characteristic, mechanical properties, semi-solid formed, hardness, spherical ? particle, eutectic compound